2005
DOI: 10.2174/1568008054863745
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Contraception in Men

Abstract: All major advances in the development of hormonal methods of contraception over the past 40 years have been exclusively female orientated with male hormonal contraception forever "just around the corner". Despite this, the last few years have seen a significant increase in the pace of research and increased involvement from the pharmaceutical industry. This is essential if the progress derived from the public sector is to be translated into a real product for widespread use. Current male methods of contracepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…Several current approaches for male contraception are based on androgen administration. For example, in clinical trials, testosterone or derivatives of it have been tested as a contraceptive to suppress the secretion of LH and follicle-stimulating hormone from the pituitary (32,33). The idea is that by depriving the testes of the signals required for local production of testosterone, normal spermatogenesis would be blocked.…”
Section: Discussionmentioning
confidence: 99%
“…Several current approaches for male contraception are based on androgen administration. For example, in clinical trials, testosterone or derivatives of it have been tested as a contraceptive to suppress the secretion of LH and follicle-stimulating hormone from the pituitary (32,33). The idea is that by depriving the testes of the signals required for local production of testosterone, normal spermatogenesis would be blocked.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease of only 20% of normal in the intratesticular testosterone level in rats was sufficient to cause an arrest of spermatogenesis. 15,16 Exogenously administered testosterone has been proposed as a contraceptive in the male by suppressing LH and FSH from the pituitary. Two studies funded by the World Health Organization have shown that azoospermia can be produced by testosterone injections in 60% to 70% of Caucasians and 95% of Asian men.…”
Section: Discussionmentioning
confidence: 99%